Discovery and segmentation method in micro-blog topics based on public emotional engagement analysis - Chunhua JU; Fuguang BAO; Junyan DAI (Dianxin kexue)
To improve the discovery efficiency and quality of micro-blog topic,a method of rapid discovery and segmentation in micro-blog topics based on public emotional engagement analysis was proposed,it would prompt evolution of the topics,then generate new topics and gain emotional change trend.Firstly,common emotional words were mined from corpus to build emotional thesaurus based on emotional word dictionary and TFDF.Then,emotional text was extracted quickly and sigmoid function was utilized to detect the intensive period of emotional engagement,ensuring the validity of topic mining.Besides,an improved adaptive FCM was used to cluster and discover topics.The experimental results show that this method can enhance the efficiency and quality of topic discovery in mobile environment.